2015
DOI: 10.3357/amhp.4087.2015
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results of the LF/HF Ratio as an Indicator for Estimating Difficulty Level of Flight Tasks

Abstract: As the LF/HF ratio turned out to be significantly higher in the zone than pre- and postflight, this parameter can be useful for predicting the risk of excessive stress and arousal of pilots during flights. Based on the LF/HF ratio we can also estimate difficulty level of flight tasks, because our research has shown higher values of this parameter in the training zone flights than in simple circle flights.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 0 publications
2
14
1
Order By: Relevance
“…Regarding the spectral analysis, in our experiment, the increase of LF/HF ratio is in accordance with the results obtained with pilots during assisted and unassisted flight, where arousal is modulated by the flight task complexity (Skibniewski et al, 2015). According to our results, the LF/HF increase is due to the HF decrease (diminution of the parasympathetic influence).…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the spectral analysis, in our experiment, the increase of LF/HF ratio is in accordance with the results obtained with pilots during assisted and unassisted flight, where arousal is modulated by the flight task complexity (Skibniewski et al, 2015). According to our results, the LF/HF increase is due to the HF decrease (diminution of the parasympathetic influence).…”
Section: Discussionsupporting
confidence: 90%
“…HRV and cognition background HRV has been found to be reactive to mental workload and stress [ 15 ] in multiple contexts, e.g., various tests requiring executive functions [ 16 ], during aircraft piloting [ 17 ], and in computer work [ 18 , 19 ]. Among others, Thayer et al [ 20 ] and Lane et al [ 21 ] have described integrative models of neural structure and autonomic regulation, and presented supporting studies which link cognition and HRV.…”
Section: Introductionmentioning
confidence: 99%
“…In more advanced tasks like driving, some investigators similarly showed that SDNN failed to differentiate between varying difficulty levels during n-back memory recall tasks (Mehler et al 2011); however, Mehler et al (2011) did suggest that other time-domain HRV metrics (e.g., RMSSD) may be more useful in cognitive demand during driving, concluding that physiological measures need to be selected carefully depending on what aspects of workload are of interest. Specific to aviation, several studies focused on flight tasks and flight simulation (Dussault et al 2004;Dussault et al 2005;Skibniewski et al 2015;Wei et al 2014a) and concluded that HRV was not as sensitive to varying cognitive demands as other physiological signals (G. F. Wilson 2002). From the systematic review (Charles and Nixon 2019), the general conclusion on HR and HRV was that their ability to distinguish mental workload was influenced by application domain, task duration, and task factors.…”
Section: Physiological Signals At the Scenario Levelmentioning
confidence: 99%